Indicator condition-guided HIV testing with an electronic prompt in primary healthcare: a before and after evaluation of an intervention. (24th January 2019) - Cayuelas Redondo, Laia; Ruíz, Marina; Kostov, Belchin; Sequeira, Ethel; Noguera, Pablo; Herrero, Maria Alba; Menacho, Ignacio; Barba, Olga; Clusa, Thaïs; Rifa, Benet; González de la Fuente, Eva María; González Redondo, Eva; et al.
Abstract : Objective: Indicator condition (IC)-guided HIV testing is a strategy for the diagnosis of patients with HIV. The aim of this study was to assess the impact on the proportion of HIV tests requested after the introduction of an electronic prompt instructing primary healthcare (PHC) physicians to request an HIV test when diagnosing predefined IC. Methods: A prospective interventional study was conducted in 2015 in three PHC centres in Barcelona to assess the number of HIV test requests made during the implementation of an electronic prompt. Patients aged 18–65 years without HIV infection and with a new diagnosis of predefined IC were included. The results were compared with preprompt (2013) and postprompt data (2016). Results: During the prompt period, 832 patients presented an IC (median age 41.6 years [IQR 30–54], 48.2% female). HIV tests were requested in 296 individuals (35, 6%) and blood tests made in 238. Four HIV infections were diagnosed (positivity rate 1.7%, 95% CI 0.5% to 4.4%). The number of HIV tests requested based on IC increased from 12.6% in 2013 to 35.6% in 2015 (p<0.001) and fell to 17.9% after removal of the prompt in 2016 (p<0.001). Younger patient age (OR 0.97, 95% CI 0.96 to 0.98), birth outside Spain (OR 1.53, 95% CI 1.06 to 2.21) and younger physician age (OR 0.97, 95% CI 0.96 to 0.99) were independent predictive factors for an HIV test request during the prompt period. The electronic prompt (OR 3.36, 95% CI 2.70 to 4.18) was the factor most closely associated with HIV test requests. It was estimated that 10 (95% CI 3.0 to 26.2) additional new cases would have been diagnosed if an HIV test had been performed in all patients presenting an IC. Conclusions: A significant increase in HIV test requests was observed during the implementation of the electronic prompt. The results suggest that this strategy could be useful in increasing IC-guided HIV testing in PHC centres.